Mercury in municipal solid waste in China and its control: a review - Cheng, Hefa; Hu, Yuanan (Environmental science & technology, 2012)
Although a potentially significant and preventable source of environmental pollution, mercury in municipal solid waste (MSW) has not received adequate attention in China. Discarded mercury-containing products, if not recycled, ultimately release mercury to air, soil, and groundwater, even after being properly collected and disposed of in MSW management facilities. This review presents an overview on mercury in MSW and describes the emissions associated with landfilling, incineration, and composting in China. Besides end-of-pipe technologies for controlling mercury emissions from MSW management, strategies for controlling mercury in MSW are also discussed, focusing on mercury source reduction and recycling. Batteries and fluorescent lamps contribute to approximately three-quarters of mercury in MSW, and are expected to remain as significant sources of mercury in the near future. Reducing or eliminating the mercury contents in household products, particularly batteries and fluorescent lamps, should be the top priority in controlling mercury in MSW, while it is also important to set mercury contents in consumer products at acceptable and achievable levels based on a life-cycle approach. Meanwhile, cost-effective recycling programs should be developed targeting products containing elemental mercury, such as medical thermometers and sphygmomanometers, and waste products with high mercury contents (e.g., button cells) as well.